KELAYAKAN DAUN JAMBU BIJI DENGAN PENAMBAHAN TEPUNG BERAS SEBAGAI MASKER UNTUK PERAWATAN KULIT WAJAH BERJERAWAT - Fitri Dewita; Rahmiati Rahmiati (Universitas Negeri Padang, 2022)
This study aims to 1) analyze how to make guava leaf mask with the addition of rice flour for acne facial skin care, 2) analyze the feasibility of guava leaf mask judging by vitamin C and flavonoid content, 3) analyze the feasibility of guava leaf mask and rice flour from texture, aroma, entanglehold and favorite panelists. The study used a quantitative approach with experimentation. The object of this study is guava leaves with the addition of rice flour made into natural mask powder. The variables in this study were free variable (X) guava leaves and bound variables (Y) of acne-free facial skincare. The type of data used in this study is primary data. Data retrieval techniques using documentation, observation. The data is analyzed by using the percentage formula to see eligibility. The results of the study were based on the content of Vitamin C and Flavonoids on guava leaf masks useful for acne facial skin care, protecting the skin from free radical attacks and Flavonoids serve as antibacterial, antioxidant and can inhibit bleeding on the skin. The appropriateness of the guava leaf mask and rice flour seen from the organoleptic test results in the texture aspect at a ratio of 60:40, most of the panelists stated that 57.14% was very smooth, while the aroma at the ratio of 80:20 most of the panelists stated that 42.8% was very strong, and adhesion power in the ratio 70:30 most of the panelists stated 57.14% adhesiveness. Meanwhile, for the hedonic test or panelists' preference in the ratio of 80:20, most of the panelists said that 57.14% really liked it. And it is hoped that further research on the feasibility of guava leaf masks and rice flour can be further developed and refined in the future to see the shelf life of masks.